Investor Sentiment, Stock Returns, and Volatility in China's A-share Market - Wang, Jiaying (2021)
Between January 2011 and April 2021, we investigate whether investor sentiment can influence stock returns and volatility in the Chinese A-share market. We also analyse the impact of rational and irrational sentiment on the stock market and the strength of the impact separately. This study uses five fundamentals and AR(1) regressions on investor sentiment, capturing partly rational sentiment and partly irrational sentiment in the residuals. The fundamentals are economic growth, inflation, interest rates, RMB/USD exchange rate and terms of trade. The time horizon is one month. The dissertation then uses a VAR model and a generalised impulse function to examine the impact of rational and irrational sentiment on the returns and volatility of the Chinese A-share market. We find that both rational and irrational sentiments are significant in the Chinese A-share market. Irrational sentiment accounts for more than 70%, much larger than the share of rational sentiment. The study shows that investors' rational and irrational beliefs are positively correlated with stock returns. When each of the two sentiments is subjected to a standard deviation shock, the path adjustments of China A-share returns are 36% and 10%, respectively. Thus rational sentiment has a more significant impact on stock returns. Moreover, the effect of irrational sentiment on stock returns does not appear until four steps later. This effect is therefore lagged. In examining the impact of investor sentiment on equity volatility, we find that only rational sentiment had a significant negative impact on equity volatility. The impact is -1%. Irrational sentiment has no material impact on equity volatility. Finally, our research may provide valuable insights for investors as they look for better investment opportunities to generate higher returns. In addition, policymakers can stimulate the stock market and reduce uncertainty by adjusting the economic environment.